JARVIS: REVOLUTIONIZING LEAD MANAGEMENT THROUGH REAL-TIME INTELLIGENCE - Achyuth Reddy Lakhireddy, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2025)
Jarvis emerges as a groundbreaking real-time transactional data platform revolutionizing lead management and customer journey optimization in today's digital landscape. Through its sophisticated microservices-driven architecture, advanced analytics capabilities, and automated decision-making systems, Jarvis transforms how organizations process, analyze, and act on customer data. The platform leverages cutting-edge technologies including Apache NiFi, Kafka, Redis, and Kubernetes to deliver seamless data processing and real-time insights. From enhanced operational efficiency to improved decision-making capabilities, Jarvis demonstrates transformative benefits across various industries, establishing new standards in lead qualification, customer engagement, and sales optimization. With continuous evolution in its capabilities and a robust technological roadmap, Jarvis stands as a pivotal solution for organizations seeking excellence in customer acquisition and relationship management.